International practices in pancreatic surgery - Mantke, René; Lippert, Hans; Büchler, Markus W.; Sarr, Michael G. (Springer, 2013)
"International Practices in Pancreatic Surgery" describes in great detail general and specific technical aspects of the standard resection procedures of the pancreas. Each surgical step during the pancreatic operation is precisely outlined and accompanied by drawings and photographs. The main chapters on pancreatic carcinoma, chronic and acute pancreatitis are written by the editors. An international faculty complements the texts by describing their own personal techniques. This concept offers the greatest possible overview of the techniques used by experienced surgeons.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Operationstechnik; Bauchspeicheldrüsenchirurgie